An artificial intelligence–based model for prediction of atrial fibrillation from single-lead sinus rhythm electrocardiograms facilitating screening. Issue 4 (7th March 2023) - Hygrell, Tove; Viberg, Fredrik; Dahlberg, Erik; Charlton, Peter H; Kemp Gudmundsdottir, Katrin; Mant, Jonathan; Hörnlund, Josef Lindman; Svennberg, Emma
Abstract: Aims: Screening for atrial fibrillation (AF) is recommended in the European Society of Cardiology guidelines. Yields of detection can be low due to the paroxysmal nature of the disease. Prolonged heart rhythm monitoring might be needed to increase yield but can be cumbersome and expensive. The aim of this study was to observe the accuracy of an artificial intelligence (AI)-based network to predict paroxysmal AF from a normal sinus rhythm single-lead ECG. Methods and results: A convolutional neural network model was trained and evaluated using data from three AF screening studies. A total of 478 963 single-lead ECGs from 14 831 patients aged ≥65 years were included in the analysis. The training set included ECGs from 80% of participants in SAFER and STROKESTOP II. The remaining ECGs from 20% of participants in SAFER and STROKESTOP II together with all participants in STROKESTOP I were included in the test set. The accuracy was estimated using the area under the receiver operating characteristic curve (AUC). From a single timepoint ECG, the artificial intelligence–based algorithm predicted paroxysmal AF in the SAFER study with an AUC of 0.80 [confidence interval (CI) 0.78–0.83], which had a wide age range of 65–90+ years. Performance was lower in the age-homogenous groups in STROKESTOP I and STROKESTOP II (age range: 75–76 years), with AUCs of 0.62 (CI 0.61–0.64) and 0.62 (CI 0.58–0.65), respectively. Conclusion: An artificial intelligence–enabled network has the ability to predict AF from a sinus rhythm single-lead ECG. Performance improves with a wider age distribution. Graphical Abstract: Graphical Abstract